Effects of topical mitomycin C on primary trabeculectomies and combined procedures. Issue 11 (November 1993) - Costa, V P; Moster, M R; Wilson, R P; Schmidt, C M; Gandham, S; Smith, M
Abstract : The charts were reviewed of all patients who underwent primary trabeculectomies (group 1) or combined procedures (phacoemulsification + intraocular lens implantation + trabeculectomy--group 2) and received intraoperative mitomycin C (0.4 mg/ml) between 1991 and 1992 at Wills Eye Hospital. A total of 54 eyes of 54 patients were included: 39 in group 1 and 15 in group 2. Intraocular pressure was controlled successfully in 97.4% of eyes in group 1 (mean follow up 6.7 months), and in 93.3% in group 2 (mean follow up 6.8 months). Main complications included choroidal detachment (n = 15), shallow anterior chamber (n = 9), cataract formation (n = 8), and hypotony maculopathy (n = 3). The use of mitomycin C in primary trabeculectomies and combined procedures is associated with high success rates. However, it may be associated with unacceptable risks of vision threatening complications related to excessive filtration.